2016
DOI: 10.1093/nar/gkw257
|View full text |Cite
|
Sign up to set email alerts
|

deepTools2: a next generation web server for deep-sequencing data analysis

Abstract: We present an update to our Galaxy-based web server for processing and visualizing deeply sequenced data. Its core tool set, deepTools, allows users to perform complete bioinformatic workflows ranging from quality controls and normalizations of aligned reads to integrative analyses, including clustering and visualization approaches. Since we first described our deepTools Galaxy server in 2014, we have implemented new solutions for many requests from the community and our users. Here, we introduce significant e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
4,983
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 6,179 publications
(5,306 citation statements)
references
References 19 publications
6
4,983
0
2
Order By: Relevance
“…The log2/ratio (33,34) between this latter profile and that of untreated cells (Fig. 4A, Bottom) confirmed that a gain of acetylation occurred in C-DOM in cells treated with both Shh and Fgf (Fig.…”
Section: Resultssupporting
confidence: 64%
“…The log2/ratio (33,34) between this latter profile and that of untreated cells (Fig. 4A, Bottom) confirmed that a gain of acetylation occurred in C-DOM in cells treated with both Shh and Fgf (Fig.…”
Section: Resultssupporting
confidence: 64%
“…Paired-end alignments adjusted by MMR may lack conformity if the fragments are too small and/or the reads align entirely to direct repeats, so we removed these particular cases to avoid uncertainty. Genome-wide coverage was computed for every library by deepTools v2.5.3 [88], taking into consideration the extension of entire fragments for paired-end alignments and the fact that orphan R2 reads align to the opposite strand of the real RNA fragment. Furthermore, we used bedtools v2.2.26 [89] to compute 5ʹ and 3ʹ profiles for each library, employing the aligned R1 and R2 reads, respectively, once more taking into consideration the orientation of reads in relation to the original RNA fragment in the sample.…”
Section: Methodsmentioning
confidence: 99%
“…The resulting candidate peaks for MLE wt and its four mutants were used to calculate pairwise Spearman correlations between all replicates (Supplemental Fig. S1G), showing increased pairwise correlations between biological replicates within each condition over replicates of differing experimental conditions (deeptools version 2.3.5) (Ramírez et al 2016). JAMM combined the MLE-binding sites located on roX1 and roX2 into single large regions.…”
Section: Methodsmentioning
confidence: 99%